NATIONAL VALUES AND FAMILY - Burkhanova Dilnoza (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on the preservation of our people's centuries-old spiritual values and traditions, traditions and customs, spiritual, educational, cultural heritage. Morality is an integral part of our national values. The issue of educating the younger generation in the spirit of love and respect for their people, their values, traditions, language and culture based on the principles of legality is widely covered.